2010
DOI: 10.4067/s0718-27242010000400002
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Open Innovation: Case China

Abstract: The notion of open innovation suggests that firms can boost their innovative performance by both acquiring knowledge from outside the company and deploying external paths to market for commercialization of non-core technologies. As innovations emerge increasingly from interorganisational cooperation, the background for such cooperation can also have an impact on the involvement of companies into open innovation processes. Thereby this paper proposes to analyze the barriers towards open innovation from three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 26 publications
2
44
0
8
Order By: Relevance
“…The underdeveloped state of markets for technology transactions also presents a barrier to outbound open innovation practices (Savitskaya, Salmi, and Torkkeli, 2010). These limitations in China's current innovation system tend to hinder its progress towards openness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The underdeveloped state of markets for technology transactions also presents a barrier to outbound open innovation practices (Savitskaya, Salmi, and Torkkeli, 2010). These limitations in China's current innovation system tend to hinder its progress towards openness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of domestic firms still maintain strict privacy of operational and strategic information, driven partially by unfavourable social cultural norms, a weak IP protection environment, and a complex IP rights legislation system (Savitskaya, Salmi, and Torkkeli, 2010). The underdeveloped state of markets for technology transactions also presents a barrier to outbound open innovation practices (Savitskaya, Salmi, and Torkkeli, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, in terms of outside-in open innovation for the process necessary for the absorption capacity as the ability to integrate knowledge may vary, because one firm can better use the internal knowledge while the others can use more externally obtained knowledge (Todorova & Durisin, 2007). Østergaard et al (2011) Savitskaya, Salmi & Torkkeli (2010) revealed that the economic systems and institutions can have a huge effect on the firm's behavior and respect. The importance of uniqueness can vary in the processes of knowledge buying and selling.…”
Section: Factors For the Outside-in Open Innovation Process And Customentioning
confidence: 99%